Emosi pekerja, gangguan kejaya-keluarga dan luapan emosi : satu kajian empirik di sebuah universiti awam di Malaysia timur - Andy, Bin Abdul Razak (Universiti Malaysia Sarawak, (UNIMAS), 2008)
This study was conducted to measure the effect of work-family interference on the relationship between emotional labour and job burnout. A survey research method was used to gather 103 usable questionnaires from an academic staffs who have worked in one public university in East Malaysia (UAMT). Outcomes of stepwise regression analysis showed two important findings : Firstly, the relationship between surface acting and work-family interference positively and significantly with job burnout. Secondly, the relationship between deep acting and work-family interference positively and significantly correlated with job burnout. This result comfirms that work-family interference does act as a full mediating variable in the emotional labour model of the studied organization.